2017
DOI: 10.1007/s11207-017-1092-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pulses of Dynamic Coupling Between Solar Hemispheres

Abstract: North-south (N-S) asymmetry of solar activity is a known statistical phenomenon but its significance is difficult to prove or theoretically explain. Here we consider each solar hemisphere as a separate dynamical system connected with the other hemisphere via an unknown coupling parameter. We use a non-linear dynamics approach to calculate the scale-dependent conditional dispersion (CD) of sunspots between hemispheres. Using daily Greenwich sunspot areas, we calculated the Neumann and Pearson chi-squared dista… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…However, in an our earlier analysis it is found that the cycle-maximum is not always occurring first in one particular hemisphere (Javaraiah 2019). The physical process responsible for the north-south asymmetry in solar activity as well as its relation to variations in solar activity is not clear yet (Volobuev and Makarenko 2017;Badalyan and Obridko 2017;Schüssler and Cameron 2018;Nepomnyashchikh et al 2019). Recently, it is suggested that there could be influence of some specific configurations of the giant planets in the origin of the well-known ≈12-year and 40 -50-year periodicities in the north-south asymmetry of solar activity (Javaraiah 2020).…”
Section: Introductionmentioning
confidence: 86%
“…However, in an our earlier analysis it is found that the cycle-maximum is not always occurring first in one particular hemisphere (Javaraiah 2019). The physical process responsible for the north-south asymmetry in solar activity as well as its relation to variations in solar activity is not clear yet (Volobuev and Makarenko 2017;Badalyan and Obridko 2017;Schüssler and Cameron 2018;Nepomnyashchikh et al 2019). Recently, it is suggested that there could be influence of some specific configurations of the giant planets in the origin of the well-known ≈12-year and 40 -50-year periodicities in the north-south asymmetry of solar activity (Javaraiah 2020).…”
Section: Introductionmentioning
confidence: 86%